Understand teacher resilience. A systematic look (Revista Innova Educación, 2021)
The objective was to carry out a systematic review on the concept of teacher resilience, the characteristics of resilient teachers, and the search for the main strategies that can serve to improve teacher resilience. The information management was done in an extended way and without the segment of years publication of different scientific articles. As a result, the concept of resilience is redefined as a capacity, process, and ability that encompass the emotional, motivational, and social dimensions of the teacher. Among the characteristics of a resilient teacher, humor, confidence, self-esteem, problem-solving, optimism, and interest in technology stand out. The strategies that serve to improve resilience derive from the psychological, pedagogical, and linguistic-sociological.
Keywords: strategies; resilience; teacher resilience